Kajian Rute Angkutan Kota di Kota Palangka Raya - Mirsa Lorensya; Desi Riani; Murniati (Jurnal Serambi Engineering, 2024)
City transportation in Palangka Raya City once had 7 routes. However, this route is no longer operational. Due to the lack of public interest in using city transport, transport operators run free routes in order to reduce losses. This research aims to analyze whether the city transport route services in Palangka Raya City are in accordance with passenger potential and evaluate city transport routes in Palangka Raya City. The method used in this research is a quantitative research method. Quantitative method, namely a method carried out systematically and using mathematical models. The results of this research can be concluded that existing route services cannot reach areas with large passenger potential, because there are still several areas with large public services and high population density but which are not yet reached by city transport